Implementation of Adolescent Education Methods in the Qur'an - Faridatul Miladiyah; Ahmad Azmi Ahsantu Dhonni; Muhammad Barnaba Ridho Ilahi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
The Qur'an is Muslims' main miracle and encompasses values covering all aspects of life, including education methods. In the Qur'an, various methods are offered for education, such as dialogue, lectures, analogies, stories, advice, wisdom, rewards and punishments, and others. This article discusses implementing teenage education methods found in the Qur'an at SMAS Islam Roudlotun Nasyiin in Mojokerto Regency. This institution is relevant to the theme being discussed: teenagers entering adulthood. The research method used in this study is qualitative, employing two types of research: library research and field research. The survey results indicate that the most favored implementation of teenage education methods from the Qur'an at SMAS Islam Roudlotun Nasyiin is the dialogue method, which involves active interaction between teachers and students. However, this does not mean that other methods are neglected. Besides the dialogue method, habituation is also consistently practiced, such as performing Mutlaq sunnah prayers, giving alms, reading the Qur'an, and greeting teachers upon arrival at school. These methods aim to shape good morals and habits in teenagers.